Modified Reduced Common Mode Current Modulation Techniques for Z-Source Inverter used in Photovoltaic Systems - Erginer, Volkan; Sarul, Mustafa Hadi (IEEE, 2013)
In photovoltaic power generation systems, it is possible to use transformerless inverters due to their high efficiency, low cost and small volume. Z-Source inverter is a promising transformerless topology that can buck or boost input voltage without a dc-dc converter. The main problem of transformerless inverter is lack of galvanic isolation between source and ac side, and it causes common mode leakage current in the system which results additional losses, current harmonics and a potential safety risk. In this paper two novel modified modulation techniques are presented to reduce common mode leakage current in a three phase Z-Source inverter used in a photovoltaic system. Effectiveness of the modified modulation techniques are confirmed via simulation results. Simulations are performed for different load power factors and switching frequencies to provide a certain comparison between conventional and proposed modulation techniques. The results are analysed considering both leakage current and inverter output current quality, and the results verify effectiveness of the proposed techniques.
Keywords: transformerless; Z-Source Inverter; common mode current; Engineering